Memory for between‐list and within‐list information in amnesic patients with temporal lobe and diencephalic lesions. Issue 1 (17th March 2014) - Hunkin, Nicola M.; Awad, Mohammed; Mayes, Andrew R.
<x xml:space="preserve">Abstract</x> Patients with medial temporal lobe damage and diencephalic damage were compared on two tests of verbal temporal order memory: between‐list discrimination and within‐list discrimination. Both patient groups were impaired relative to a group of healthy control participants. In addition, despite comparable levels of item recognition, the diencephalic group was impaired relative to the medial temporal lobe group on both within‐list and between‐list discrimination. Temporal order memory for between‐list information showed a significant correlation with a composite measure of recognition memory, and the results are discussed in terms of the patients' reliance on familiarity and distance‐based processes to make temporal order judgments.